Seminar and Speak-Out on the War in Iraq - Sherman, Daniel; Nardin, Terry; Paik, Peter Y.; Allen, David S.; Dobkin, Joan; Galvao-Sobrinho, Carlos; Mamalakis, Markos; Shashko, Philip; Brodwin, Paul; van Dijk, Rutger; Hamdani, Abbas; Jay, Greg; et al. (My University, 2003)
In this working paper, topics concerning different aspects of the Iraq war are presented and then discussed. Topics include: who can authorize a war, intellectual foundations for new imperialism, the role of media in war, and the theft of Iraq's culture as a result of the war.
Keywords: Iraq war; foreign policy; media in war; iraq culture